2001
DOI: 10.1023/a:1014739131690
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Once cancer cells have spread and formed secondary masses, breast cancers are largely incurable even with state-of-the-art medicine. To improve diagnosis and therapy, better markers are needed to distinguish cells which have a high probability for causing clinically relevant, macroscopic metastases. In this review, we summarize the several genes that regulate breast cancer metastasis. Two categories of genes are presented--metastasis activator (ras, MEK1, mta1, proteinases, adhesion molecules, chemoattractants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Hs␣ (HP1 Hs␣ ) 3 was found to be down-regulated (1.5-fold) in highly invasive metastatic breast cancer cell lines compared with poorly invasive nonmetastatic breast cancer cell lines (8,9). Consistent with this reduction in mRNA, HP1…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Hs␣ (HP1 Hs␣ ) 3 was found to be down-regulated (1.5-fold) in highly invasive metastatic breast cancer cell lines compared with poorly invasive nonmetastatic breast cancer cell lines (8,9). Consistent with this reduction in mRNA, HP1…”
mentioning
confidence: 98%
“…Invasion is one of the first steps in the metastatic cascade and is a strong indicator of tumor progression. Two classes of proteins have been identified that regulate metastasis progression: activators and suppressors (3). Metastasis activators are genes that promote metastasis, whereas metastasis suppressors inhibit metastasis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the cause of MGT is related to the hormone values [13], however, the molecular process for development of metastasis is still unclear. In studies examining the relationship between the development of metastasis and nm23 expression levels in human breast cancer, it has been suggested that nm23 genes may be one of the metastatic suppressor genes [3,17]. In the present study, we focused on the function of nm23 genes in the metastasis of canine MGT.…”
mentioning
confidence: 97%
“…88,92 Based on these data, HP1a has now been characterized as a metastasis suppressor, 88,92 which in contrast to tumor suppressors are defined as being able to suppress metastasis without affecting the growth of the tumor. 94 On the surface it seems contradictory that up-regulation of HP1a correlates with increased cell proliferation of the primary tumor and poorer clinical prognosis while downregulation of HP1a contributes to a tumor cell's invasive potential during carcinogenesis. Closer inspection suggests that these observations constitute primary examples of the global inverse correlation that exists between cancer cell proliferation and invasion.…”
mentioning
confidence: 99%